1994
DOI: 10.1089/thy.1994.4.147
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of a Variant Human Thyrotropin Receptor (hTSHR) Gene

Abstract: Sequencing of the human thyrotropin receptor (hTSHR) gene using genomic DNA from peripheral blood leukocytes revealed a substitution of nucleotide 253 in the cDNA sequence. The replacement of the wild-type cytosine-253 to adenine results in the replacement of the wild-type Pro at codon 52 (CCC) with Thr (ACC) located in exon 1 of the TSHR. We screened genomic DNAs from 60 unrelated individuals for the presence of A253 by PCR amplification using a degenerate oligonucleotide primer that produces a Tth111 I restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 11 publications
2
24
0
Order By: Relevance
“…However, the (Pro52Thr) variant was firstly reported by Bohr [31] and believed to have an effect on Graves' disease. In another study, Sunthornthepvaraku [32] showed the (Pro52Thr) variant was a polymorphism. It was found in 12% of the normal individuals studied and not linked to any thyroid abnormalities.…”
Section: Discussionmentioning
confidence: 94%
“…However, the (Pro52Thr) variant was firstly reported by Bohr [31] and believed to have an effect on Graves' disease. In another study, Sunthornthepvaraku [32] showed the (Pro52Thr) variant was a polymorphism. It was found in 12% of the normal individuals studied and not linked to any thyroid abnormalities.…”
Section: Discussionmentioning
confidence: 94%
“…Conversely, germline loss-of-function TSHR mutations are associated with TSH resistance and congenital hypothyroidism (see reference (8) for an illustrative example). However, only three germline TSHR polymorphisms, resulting in amino acid substitutions, have been identified (9)(10)(11). Two of these are located in the extracellular domain of the receptor (Asp36His and Pro52Thr) (9,10), and one is located in the intracellular domain (Asp727Glu) (11) (Fig.…”
Section: Polymorphisms In the Tsh Receptormentioning
confidence: 99%
“…The response to bioactive TSH may be impaired at the level of the thyrocyte (figure 2) (33)(34)(35). Total insensitivity to TSH results in a small hypoplastic thyroid gland and reduced synthesis and secretion of thyroid hormones.…”
Section: Resistance To Tshmentioning
confidence: 99%
“…In partial resistance, TSH levels are elevated, but the peripheral hormones are normal, a constellation referred to as euthyroid hyperthyrotropinemia (33). In these patients, the size of the thyroid is normal or enlarged.…”
Section: Tsh Receptormentioning
confidence: 99%